Академічні зібрання творів Тараса Шевченка: історія і сучасність (до сторіччя НАН України) - Боронь, О.В.; Росовецький, С.К.; Назаренко, М.Й.; Харчук, Р.Б.; Карпінчук, Г.В.; Лебідь-Гребенюк, Є.М. (Слово і Час, 2019)
Круглий стіл під такою назвою відбувся 1 листопада 2018 р. в Інституті літератури. Відкриваючи засідання, заступник директора з наукової роботи акад. НАН України М. Сулима наголосив на необхідності поглибленого вивчення історії академічних видань Шевченкових творів, щоб у роботі над проектованим новим повним зібранням урахувати позитивний, а подекуди і драматичний досвід попередників. Заступник директора з наукової та видавничої діяльності С. Гальченко у виступі “Академічне видання української класики: перспективи за сучасних безперспективних умов” окреслив основні труднощі, які негативно впливають на функціонування книговидавничого ринку в Україні. Із презентацією “Електронна колекція, оцифроване і цифрове видання: Повне зібрання творів Шевченка у мережі” виступив молодший науковий співробітник відділу шевченкознавства Д. Єсипенко. Пропонуємо увазі читачів стислий виклад повідомлень учасників круглого столу. A round table under the above mentioned name was held on November 1, 2018 at the Institute of Literature. O. Boron focused on the principles of a new academic edition, proposing to confine it to Shevchenko’s literary heritage. While according to S. Rosovetskyi, one may try to arrange verbal texts and works of figurative art in each volume chronologically or in such a sequence of genres in verbal volumes: poetry, prose, drama, folklore records, diary, letters, articles, gift inscriptions, business papers. S. Rosovetskyi also submitted arguments in favor of returning the dates and places of writing specified by the author to the end of the published texts. He refused the idea of including a poem “Stoyit v seli Subotovi…” (“There stands in Subotiv village…”) into the text of “Velykyi Liokh” (“The Great Vault”), and supported the principle of publishing all the author’s variants, the elaboration of the comparative component in the comments, etc. R. Kharchuk analyzed Shevchenko’s works of fine art “Death of Bohdan Khmelnytskyi” (1836–1837), “Cossack Banquet” (1838), and “Gifts in Chyhyryn, 1649” (1844), defining the historical sources used by the artist. M. Nazarenko focused on the written forms of the word “Boh” (“God”), i. e. on the usage of the uppercase or lowercase initial letter in the manuscripts of Shevchenko’s poetry. He showed that the author’s choice in this case was related to the time when the autograph appeared: in 1840–1847 the lowercase initial letter prevailed, while in 1857–1859 the uppercase one. The researcher specified the cases where deviations from these regularities could be semantically grounded. The report of H. Karpinchuk “Not named by name: the participation of repressed Shevchenko researchers in preparation of the academic editions of Taras Shevchenko’s works” was focused on personalities of the scholars whose efforts considerably contributed to the preparation of the first two editions. It was emphasized that none of the researchers specializing in Shevchenko’s heritage could avoid the persecution of the People’s Commissariat of International Affairs in the late 1920s – early 1930s. Ye. Lebid-Hrebeniuk reviewed five editions of Taras Shevchenko’s complete collection of works, published by the Academy of Sciences at various times. According to the researcher the main characteristics common to all publications are completeness, academically grounded comments, attention to the needs of the recipient (necessary references and indices).